PENYUSUNAN MODUL PEMBELAJARAN JARINGAN TUMBUHAN BERBASIS HAKIKAT SAINS - Evi Mardiani; Siti Romlah Noerhodijah (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2015)
This research aimed to develop a learning module on plant tissue based on the nature of science and to analyse the module quality based on the experts. This research was a development research (R&D) with3-(Define, Design, and Develop) model. The instruments in this research were questionnaire and assessment questionnaire. Module was assessed from the feasible aspects of content, language, presentation and graphics.The datawasconductedby assessmen tquestionnaire, and then processed quantitatively. The data was collected by questionnaire were analyzed descriptively. There sults howed learning module based on the nature ofscience on plan ttissue has a very good by assessment of the experts.